Tree Risk Assessment with Sonic Tomograph Method at Bali Botanical Garden - Hanum, Siti Fatimah; Dharma, I Dewa Putu; Atmaja, Muhammad Bima; Oktavia, Gebby Agnessya Esa (Jurnal Manajemen Hutan Tropika, 2020)
Safety perception is the most important part of people’s choice in determining tourist sites. Standing trees that are prone to falling are very dangerous for both visitors and employees. Standing tree with decay wood inside is often the cause of tree failure. Therefore, there is a need for research examining the risk of collection and non-collection trees in Bali Botanical Garden. Tree risk checks were carried out using the Tree Risk Assessment method from the International Society of Arboriculture (ISA), which has been modified. The result of this research gives valuable information for the manager to determine tree handling to minimize tree risk.